Some technological properties of laminated veneer lumber produced with fast-growing Poplar and Eucalyptus - Cihad Bal, Bekir (Maderas. Ciencia y Tecnología, 2016)
Fast-growing tree species are important due to their short growth time before they are harvested. Both the Poplar and Eucalyptus species are fast-growing trees. These two species have been cultivated in many parts of the world, and they are used in several ways, including in the pulp and paper industry, as wood-based panels, and as structural composite lumber. In this study, laminated veneer lumbers were produced using different combinations of Poplar (Populus x euramericana I-214) and Eucalyptus (Eucalyptus grandis) veneers. Some physical and mechanical properties, including density, thickness swelling, water absorption, modulus of elasticity, modulus of rupture, impact bending, and bonding performance were investigated. According to the test data that were obtained, the mechanical properties of laminated veneer lumbers produced with Eucalyptus were greater than those of laminated veneer lumbers produced with Poplar. When the two were combined and Eucalyptus was used as the top and bottom plies, the mechanical properties also were better than those of Poplar laminated veneer lumbers. As a result, it can be said that both Poplar and Eucalyptus veneers can be used to produce laminated veneer lumbers, and Poplar laminated veneer lumbers can be reinforced with Eucalyptus veneers.